Real and Pseudoaccommodation in Accommodative Lenses - Ioannis G. Pallikaris; Georgios A. Kontadakis; Dimitra M. Portaliou (Journal of Ophthalmology)
In the attempt to manage presbyopia, different intraocular lens designs have been proposed such as monofocal IOLs with monovision or multifocal IOLs. Even though the lenses mentioned offer satisfactory visual results, contemporary ophthalmology has not completely answered the presbyopic dilemma by simulating the accommodative properties of the crystalline lens itself. Accommodative IOLs were designed to fill this gap and provide satisfactory vision for all distances by restoring some degree of “pseudoaccommodation.” Pseudo accommodative capability can be linked to monofocal IOL’s as well but the results are not satisfactory enough to fully support unaided near vision. Pseudoaccommodation is a complex phenomenon that can be attributed to several static (i.e., pupil size, against-the-rule cylindrical refractive error, multifocality of the cornea) and dynamic (i.e., anterior movement of the implant itself) factors. Objective measurement of the accommodative capability offered by the accommodative IOLs is extremely difficult to obtain, and different methods such as autorefractometers, retinoscopy, and ultrasound imaging during accommodative effort, ray tracing, or pharmacological stimulation have been developed but the results are sometimes inconsistent. Despite the difficulties in measuring accommodation, accommodative IOLs represent the future in the attempt to successfully “cure” presbyopia.